Value Added Tax: and its Applicability in Nepal by Babu Ram Subedi - Sharma, Neelam Kumar (Tribhuvan University Journal, 2011)
Not necesary Key words: Value Addad Tax; Applicability; Nepal Tribhuvan University Journal Vol XXI, No. 2, 1998 Page: 163-164 Uploaded date: 29 April, 2011